PENDAMPINGAN PENGAJARAN TAJWID DAN FASHOHAH SERTA PENGUATAN MODERASI BERAGAMA DI TPQ AL-KHIDMAH DAN AL-IKHLAS - Zain, Lailatul Maghfiroh (UIN Sunan Kalijaga, 2025)
Abstract - This research is a portrait of the dedication of students participating in KKM 61 UIN Maulana Malik Ibrahim Malang in assisting the learning of tajweed and fashohah at TPQ al-Khidmah and TPQ al-Ikhlas. The main purpose of this activity is to improve the ability to read the Qur'an properly and instill religious moderation values to students from an early age. Through interviews, observations, and documentation methods, it was found that there are still many students who have difficulty reading the Qur'an according to the rules of tajweed, while the limited teaching staff is the main challenge in the learning process. As a solution, KKM students apply an integrated teaching method that combines tajweed and fashohah learning, as well as strengthening religious moderation to close the mentoring process. The results of this assistance show an increase in fluency in reading the Qur'an and the santri's understanding of moderate religious attitudes. The program was closed with Isra Mi'raj commemoration activities and khotmil Qur'an prayers as a form of strengthening religious values. This research emphasizes the importance of early Islamic education in forming a generation that is not only proficient in reading the Qur'an, but also has a balanced and tolerant understanding of religion. Keywords: TPQ Mentoring, Tajweed, Fashohah, Religious Moderation. Abstrak - Penelitian ini merupakan potret pengabdian mahasiswa peserta KKM 61 UIN Maulana Malik Ibrahim Malang dalam mendampingi pembelajaran ilmu tajwid dan fashohah di TPQ al-Khidmah dan TPQ al-Ikhlas. Tujuan utama dari kegiatan ini adalah meningkatkan kemampuan membaca Al-Qur’an dengan baik serta menanamkan nilai-nilai moderasi beragama kepada santri sejak dini. Melalui metode wawancara, observasi, dan dokumentasi, ditemukan bahwa masih banyak santri yang mengalami kesulitan dalam membaca Al-Qur’an sesuai kaidah tajwid, sementara keterbatasan tenaga pengajar menjadi tantangan utama dalam proses pembelajaran. Sebagai solusi, mahasiswa KKM menerapkan metode pengajaran terpadu yang mengombinasikan pembelajaran tajwid dan fashohah, serta penguatan moderasi beragama sebagai penutupan proses pendampingan. Hasil dari pendampingan ini menunjukkan adanya peningkatan dalam kefasihan membaca Al-Qur’an serta pemahaman santri mengenai sikap beragama yang moderat. Program ini ditutup dengan kegiatan peringatan Isra Mi’raj dan doa khotmil Qur’an sebagai bentuk penguatan nilai-nilai keagamaan. Penelitian ini menegaskan pentingnya pendidikan Islam sejak dini dalam membentuk generasi yang tidak hanya mahir dalam membaca Al-Qur’an, tetapi juga memiliki pemahaman agama yang seimbang dan toleran. Kata Kunci: Pendampingan TPQ, Tajwid, Fashohah, Moderasi Beragama.